The Visual Impact of IBM in the Earliest Spanish Magazines Headers in Computing for Final Users - Jiménez Narros, Carlos (Estudios sobre el Mensaje Periodístico, 2013)
In the early eighties coexist a wide range of computers –Commodore, Sinclair, Amstrad– but IBM (International Business Machines) is the brand that wins the battle in the market for personal computers, compatible Personal Computer (PC). The current IBM logo was designed by Paul Rand in the midfifties and after the international projection of this company, its visual appearance causes a strong influence and begins to be imitated by companies, institutions, computer stores, electronics shops and more specifically for the publishing of magazines especialized in computing for final users. This research brings us back to the first Spanish headers specialized in computer users and especially for those in which this influence is evident. This analysis is part of a large research titled: Design evolution of computer magazines for advanced users in Spain. This research brings us back to the earliest Spanish headers specialized in computing for users and especially for those in which this influence is evident. This analysis is part of a large research titled: Design evolution of computer magazines for advanced users in Spain.